Solve for r 7-3r=r-4(2+r)

Math
7-3r=r-4(2+r)
Since r is on the right side of the equation, switch the sides so it is on the left side of the equation.
r-4(2+r)=7-3r
Simplify r-4(2+r).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
r-4⋅2-4r=7-3r
Multiply -4 by 2.
r-8-4r=7-3r
r-8-4r=7-3r
Subtract 4r from r.
-3r-8=7-3r
-3r-8=7-3r
Move all terms containing r to the left side of the equation.
Tap for more steps…
Add 3r to both sides of the equation.
-3r-8+3r=7
Combine the opposite terms in -3r-8+3r.
Tap for more steps…
Add -3r and 3r.
0-8=7
Subtract 8 from 0.
-8=7
-8=7
-8=7
Since -8≠7, there are no solutions.
No solution
Solve for r 7-3r=r-4(2+r)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top